Предмет: Математика, автор: BangtanSoneantan

помогите пожалуйста ​

Приложения:

Ответы

Автор ответа: Аноним
0

a=> (-1\frac{2}{3})^{-4}=(-\frac{5}{3})^{-4}=(-\frac{3}{5})^{4}=\frac{81}{625};\\\\b => (-1\frac{1}{2})^{-5}= (-\frac{3}{2})^{-5}=(-\frac{2}{3})^5=-\frac{32}{243};\\\\c => (3^{-1})^{5}*81^{2}=3{-5}*3^{8}=3^{3}= 27;\\\\d=>9^{-2}:3^{-6}= 3^{-4}:3^{-6}= 3^{2}=9;\\\\e => 4^{5}*16^{-2}= 4^{5}*4^{-4}= 4;\\\\f=> 32*(2^{-4})^{2}=2^{5}*2^{-8}=2^{-3}=\frac{1}{2^{3}}=\frac{1}{8} =>or<= 0,125;

Похожие вопросы
Предмет: Математика, автор: ncuxolog